2012
DOI: 10.1021/jm300535s
|View full text |Cite
|
Sign up to set email alerts
|

Selective Mode of Action of Guanidine-Containing Non-Peptides at Human NPFF Receptors

Abstract: The binding pocket of both NPFF receptors was investigated, focusing on subtype-selective behavior. By using four non-peptidic compounds and the peptide mimetics RF9 and BIBP3226 agonistic and antagonistic properties were characterized. A set of Ala receptor mutants was generated, the binding pocket was narrowed down to the upper part of transmembrane helices V, VI, VII, and the extracellular loop 2. Positions 5.27 and 6.59 have been shown to have a strong impact on receptor activation and were suggested to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 54 publications
3
15
0
Order By: Relevance
“…RF9 displayed no NPFF1R antagonism at any concentration in both cAMP and calcium mobilization tests, therefore our in vitro experiments indicate that achieving NPFF1R antagonism using RF9 in vivo would not be possible. While RF9's agonism at NPFF1R was a surprising result, we note that Findeisen et al, (24) have reported similar findings with RF9. To date, publications with pharmacological data demonstrating the function of RF9 at NPFF1R has been limited to Simonin et al, (22) and Findeisen et al, (24).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…RF9 displayed no NPFF1R antagonism at any concentration in both cAMP and calcium mobilization tests, therefore our in vitro experiments indicate that achieving NPFF1R antagonism using RF9 in vivo would not be possible. While RF9's agonism at NPFF1R was a surprising result, we note that Findeisen et al, (24) have reported similar findings with RF9. To date, publications with pharmacological data demonstrating the function of RF9 at NPFF1R has been limited to Simonin et al, (22) and Findeisen et al, (24).…”
Section: Discussionsupporting
confidence: 74%
“…While RF9's agonism at NPFF1R was a surprising result, we note that Findeisen et al, (24) have reported similar findings with RF9. To date, publications with pharmacological data demonstrating the function of RF9 at NPFF1R has been limited to Simonin et al, (22) and Findeisen et al, (24). Including our current work, there is now strong pharmacological evidence that RF9 is actually a weak, full …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…imentally. Additionally, we note that given reported Ki values (6,20), 10-to 100-fold higher concentrations of RF9 over RFRP-3 may be required to fully assess antagonistic effects of RF9 at Npff receptors. Third, RFRP-3 inhibits GnRH neurons through opening potassium channels (8) so application of RF9 to block on-going RFRP-3 transmission in the slice should result in the closure of potassium channels.…”
mentioning
confidence: 98%
“…The original studies undertaken by Simonin et al (6) reported that RF9 up to 10M did not bind Kiss1r. However, recent studies have found different binding and kinetic properties of RF9 at Npff receptors (20), and there is increasing recognition that substantial crossover exists between the different RFamide ligands and receptors (21). Nevertheless, it remains unclear how RF9 may interact with Kiss1r.…”
mentioning
confidence: 99%